Experiencias de las mujeres que trabajan y de las mujeres amas de casa en el periodo de perimenopausia - León López, Tania del Carmen (2016)
This is a qualitative study and performed with the methodology of Grounded Theory. The study is main objective is to describe the experience of women going through the perimenopausal period, in relation to the influence of the nuclear family, work, household activities and the role of women. The research was comparative type; and was investigated as a subgroup made up of women who were in charge of work activities and other subgroup comprised solely of women engaged in domestic chores. Data collection was conducted through six semi-structured interviews and focus group applied to each of the subgroups. The results of this research indicate that there are no major differences between the two subgroups with respect to symptoms, domestic activities, work activities and perception of women is role during the perimenopause. However, differences related to the age of the children were found, women with small children describe greater difficulties than those who have teenagers or adults; because young children require more care, so that women have more concerns and not have time for themselves. Moreover, among the results, women during perimenopause explain that tend to focus on themselves and enjoy more of the things that interest them.